The effect of mergers and acquisitions on the efficiency of Vietnam banking system during the restructuring period - Nguyen Phuong Anh; Thi Thanh Thuy Nguyen (Cogent Economics & Finance, 2022)
Since 2011, the Vietnamese banking system has performed many M&A deals. Some small banks which had weak competitiveness and experienced operating activities risk were on the verge of bankruptcy, and had been acquired by potential financial institutions. Although M&A transactions are known for numerous advantages which are brought back for banking industry, most banks still have not actively participated. Therefore, gaining more information about how M&A activities changed our banking system is essential for providing suitable implications and developments for the future. This report first aims to investigate the efficiency level of 30 Vietnamese commercial banks during 2011-2019 period under intermediation and operating approach using Bootstrap Data Envelopment Analysis. Next, applying Robust Truncated Regression, this paper shows that M&As negatively affect banking efficiency. Meanwhile, a set of explanatory variables following CAMELS standards can contribute to increase the efficiency level.
Keywords: 330; banking efficiency; bootstrap DEA scores; CAMELS standards; M&A